ENERGY AND SUSTAINABILITY VII. (WIT Press, 2017)
Containing papers presented at the 7th International Conference on Energy and Sustainability, this volume includes collaborative research between different disciplines, including materials, energy networks, new energy resources, storage solutions, waste to energy systems, smart grids and many other related subjects.